Form-and-fact based modeling - Halpin, Terry; Weber, Gerald (Springer Berlin Heidelberg, 2012)
A conceptual data model for an information system specifies the fact structures of interest as well as the constraints and derivation rules that apply to the business domain being modeled. Fact-based modeling approaches provide rich graphical and textual languages for specifying conceptual data models, using attribute-free fact structures that enable models to be verbalized and populated in natural sentences that are easily understood by the domain experts best qualified to validate the models. Form-based modeling approaches offer a natural way for domain users to agree upon suitable user interfaces for interacting with the information system. This paper proposes a synthesis of the two approaches, in which prototype forms are used to seed the conceptual data model, which is then used to generate the final user interface. Semantic and practical aspects of form design are discussed, and screen transition diagrams are employed to help visualize and validate the underlying dynamic processes.